Resource taxation with heterogeneous quality and endogenous reserves - CONRAD, Robert F. (Institutional Knowledge at Singapore Management University, 1981)
This paper analyzes the impact of mining taxation on the intertemporal extraction profile for a heterogeneous ore body. The extraction profile specifies both quantities and qualities extracted in each period. Total extraction is thus endogenously determined. The taxes explicitly considered are severance taxes (ad valorem or per unit; on metal or on ore), property taxes, and profits taxes (with depletion allowance). The intertemporal framework integrates economic and geological factors, generating new results on extraction distortions and providing qualification or reconciliation of previous diverse results in this area.